1820 Ind. Acts 39 - (:unkn) unknown (My University, 1820)
Ch. 11, § 1: Prohibited any person from wearing or carrying any dirk, pistol, sword-cane, or other dangerous weapon. Violators punished by fine not exceeding one hundred dollars.
Keywords: CARRY